Abductor muscle necrosis due to iliopsoas bursal mass after total hip arthroplasty - DeFrancesco, Christopher J. (J Clin Orthop Trauma, 2015)
BACKGROUND: While symptomatic iliopsoas bursal lesions have been reported after total hip arthroplasty (THA), mass effect of the collection causing abductor muscle damage has not been reported in the literature. METHODS AND RESULTS: This report discusses the presentation, clinical findings, and operative management of a patient, status post metal-on-polyethylene THA, with a large psoas bursal collection with resulting abductor muscle injury and deep venous thrombosis from compression of the femoral vein. Despite the improved wear characteristics of modern-generation THA implants, physicians must be aware of the possibility of soft tissue irritation of the iliopsoas as a cause of soft tissue swelling, persistent pain, and potential adverse complications. It is also important to recognize the variety of effects and spectrum of severity for associated lesions, including muscle damage. CONCLUSIONS: This report highlights the rare findings of abductor muscle necrosis, as well as acute thrombosis, related to iliopsoas bursitis. It also highlights a review of the available literature.